Mepolizumab for Eosinophilic Granulomatosis With Polyangiitis: A European Multicenter Observational Study. Issue 2 (30th December 2021) - Bettiol, Alessandra; Urban, Maria Letizia; Dagna, Lorenzo; Cottin, Vincent; Franceschini, Franco; Del Giacco, Stefano; Schiavon, Franco; Neumann, Thomas; Lopalco, Giuseppe; Novikov, Pavel; Baldini, Chiara; Lombardi, Carlo; et al.
Abstract : Objective: Mepolizumab proved to be an efficacious treatment for eosinophilic granulomatosis with polyangiitis (EGPA) at a dose of 300 mg every 4 weeks in the randomized, controlled MIRRA trial. In a few recently reported studies, successful real‐life experiences with the approved dose for treating severe eosinophilic asthma (100 mg every 4 weeks) were observed. We undertook this study to assess the effectiveness and safety of mepolizumab 100 mg every 4 weeks and 300 mg every 4 weeks in a large European EGPA cohort. Methods: We included all patients with EGPA treated with mepolizumab at the recruiting centers in 2015–2020. Treatment response was evaluated from 3 months to 24 months after initiation of mepolizumab. Complete response to treatment was defined as no disease activity (Birmingham Vasculitis Activity Score [BVAS] = 0) and a prednisolone or prednisone dose (or equivalent) of ≤4 mg/day. Respiratory outcomes included asthma and ear, nose, and throat (ENT) exacerbations. Results: Two hundred three patients, of whom 191 received a stable dose of mepolizumab (158 received 100 mg every 4 weeks and 33 received 300 mg every 4 weeks) were included. Twenty‐five patients (12.3%) had a complete response to treatment at 3 months. Complete response rates increased to 30.4% and 35.7% at 12 months and 24 months, respectively, and rates were comparable between mepolizumab 100 mg every 4 weeks and 300 mg every 4 weeks. Mepolizumab led to a significant reduction in BVAS score, prednisone dose, and eosinophil counts from 3 months to 24 months, with no significant differences observed between 100 mg every 4 weeks and 300 mg every 4 weeks. Eighty‐two patients (40.4%) experienced asthma exacerbations (57 of 158 [36%] who received 100 mg every 4 weeks; 17 of 33 [52%] who received 300 mg every 4 weeks), and 31 patients (15.3%) experienced ENT exacerbations. Forty‐four patients (21.7%) experienced adverse events (AEs), most of which were nonserious AEs (38 of 44). Conclusion: Mepolizumab at both 100 mg every 4 weeks and 300 mg every 4 weeks is effective for the treatment of EGPA. The 2 doses should be compared in the setting of a controlled trial.